Perancangan Brand Identity Bandung Communication and Community (Bdgcom_Unity) - Rinaldi, Mario; Pertiwi, Annisa Bela; Satyadharma, I Gede Nyoman Wisnu (Jurnal Informatika Ekonomi Bisnis, 2023)
Brand identity is an important aspect in the world of business and marketing. A strong brand identity can help a company differentiate itself from competitors, create an emotional connection with customers, and influence their perception of the products or services offered. In the current era of globalization and digitalization, brand identity is becoming increasingly relevant to gain customer attention and loyalty. This research was conducted to explain; (1) Providing a strong brand identity can provide a significant competitive advantage. Companies with a cohesive and positive brand identity tend to be more successful in retaining customers, attracting new customers, and maintaining their market share. (2) Knowing brand identity can help understand the relationship between strong brand identity and customer loyalty. Customers who feel emotionally connected to a brand are more likely to remain loyal and contribute to a company's long-term revenue; (3) knowing brand identity can also play an important role in company growth. With a strong brand, companies can more easily expand their products or services into new markets and attract investors or potential business partners. Data collection techniques focus on initial surveys, determining the problem formulation, determining research methods, processing and analyzing data, and creating a final report. The results of research on brand identity design for a company include visual communications such as logos, colors and graphic designs, as well as brand narratives in marketing messages, all of which contribute to brand identity. It is hoped that the findings of this research can provide recommendations that logos are very important in building a brand's identity.